The relationship of the University of the Philippines College of Law library's organizational culture to its staff job satisfaction - Garcia, Patricia Dianne S. (2016)
According to Edgar Schein, organizational culture is a pattern of shared assumptions that are learned by a groupthat has worked well to be taught to new members as the standard way of doing things. Studies of Ritchie (2000) and Mehr et al (2012) concluded that organizational culture affect performance and productivity. While various researchers provided that job satisfaction is dependent on organizational variables. There are only few studies about organizational culture and job satisfaction that were conducted in the Philippines and in Philippine libraries in particular. This study was conducted among the staff of the UP College of Law Library in UP Diliman and determined the relationship between the library's organizational culture to its staff job satisfaction.